496 Falls and cataract: investigating risk and predictors in older adults during their wait for surgery. (1st September 2016) - Palagyi, Anna; Rogers, Kris; Meuleners, Lynn; McCluskey, Peter; White, Andrew; Ng, Jonathon; Morlet, Nigel; Keay, Lisa
Abstract : Background: There is strong evidence of increased falls risk associated with cataract. Although cataract surgery can restore sight, lengthy waiting times are common in many high income countries, including Australia. Here, we report the risk and determinants of falls in older people with cataract during their surgical wait. Methods: Data from a prospective study of falls in a cohort of patients aged ≥65 years on Australian cataract surgery waiting lists were analysed. Participants underwent assessment of vision, comorbidity, physical activity and health-related quality of life (HRQoL), and recalled falls in the previous 12 months. Falls were also self-reported prospectively using monthly calendars; the context and outcomes of any falls were determined by interview. Results: Of 329 participants, mean age was 76 years and 55% were female. Participants' habitual vision was an average of 20/40 (20/16 to 20/160) and 10% were vision impaired (<20/60). Falling in the previous 12 months (129 [39%] participants) was associated with the use of antidepressant medication (odds ratio [OR] 3.6, 95% confidence interval [CI]: 1.7−7.5) and older age (OR 1.3, 95% CI: 1.1−1.6; five year increase in age). A total of 242 falls were reported prospectively by 98/298 (33%) participants during the surgical wait – a falls rate of 1.2 per year. Poorer vision function (incidence rate ratio [IRR] 1.1, 95% CI: 1.0−1.2), lower self-rated HRQoL (IRR 1.1, 95% CI: 1.0−1.2), increased walking activity (IRR 1.1, 95% CI: 1.0−1.1) and lower BMI (IRR 1.1, 95% CI: 1.0−1.1) were predictive of falls risk. Over one half (51%) of falls were injurious, including 11 head injuries and 2 fractures. Conclusions: These findings provide insight into associations with increased falls risk in older adults with cataract. We demonstrate the negative impact of impaired vision function on falls risk and injury, and reinforce the need for improved efficiency of surgical services to avoid escalation of this critical public health issue.